The Relationship Of Online Learning To The Quality Of Student Learning Akper HKBP Balige Year 2020 - Elfrida Nainggolan; Nurlela Petra Saragih; Jenti Sitorus (CV. AFDIFAL MAJU BERKAH, 2022)
Learning is an important factor in a person's daily life. Learning is an important factor in a person's daily life. Saiful Mujani Research and Consulting (SMRC) released data on the results of a survey conducted in the period 5 - 8 August 2020 related to online education during the Covid-19 pandemic. The results of the survey showed that 92% of students had a lot of problems participating in online learning during the corona pandemic. This type of research is cross-sectional quantitative research. The population is all Level I and II students of Akper HKBP in 2020. The sample amounted to 79 people, sampling technique is the total sampling. Data collection is done by using questionnaires, data analysis is univariate analysis, analysis and analysis of multivariate bvariety. The results of the statistical test obtained a value of p=0.000, it can be concluded that there is a relationship of online learning to the quality of student learning Akper HKBP Balige in 2020.